Moderating effects of financial cognitive abilities and considerations on the attitude-intentions nexus of stock market participation - Tahmina Akhter; Mohammad Enamul Hoque (International Journal of Financial Studies, 2022)
This study aims to examine the determinants of investors' behavioral intentions to participate in the stock market. In this attempt, this research investigated the direct and moderating effects of the financial cognitive abilities and the financial considerations on the nexus of attitudes and behavioral intentions of investors. Data for this study were collected from active and potential investors in the Dhaka Stock Exchange of Bangladesh using a structured questionnaire. The partial least squares method was used to examine the nature and extent of the relationships of investors' behavioral intentions with their attitude, financial cognitive abilities, and financial considerations in making stock market investment-related decisions. The findings of this study suggest that investors' attitudes, financial planning ability, and perceptions of financial risks and benefits are important factors that influence their decisions in stock market participation. Moreover, financial planning, financial satisfaction, and perceived financial risk moderate the nexus of attitude and behavioral intentions to participate in the stock market. This study, therefore, has significant implications for policymakers, stock market regulators, and financial service providers.
Keywords: 330; behavioral intentions; financial benefit perception; financial planning; financial risk perception; financial satisfaction; investors' attitude; stock market participation